Predicting and testing continental vertical motion histories since the Paleozoic - Zhang, Nan; Zhong, S.; Flowers, R. (Elsevier BV, 2012)
Dynamic topography at the Earth's surface caused by mantle convection can affect a range of geophysical and geological observations including bathymetry, sea-level change, continental flooding, sedimentation and erosion. These observations provide important constraints on and test of mantle dynamic models. Based on global mantle convection models coupled with the surface plate motion history, we compute dynamic topography and its history for the last 400. Ma associated with Pangea assembly and breakup, with particular focus on cratonic regions. We propose that burial-unroofing histories of cratons inferred from thermochronology data can be used as a new diagnostic to test dynamic topography and mantle dynamic models. Our models show that there are currently two broad dynamic topography highs in the Pacific and Africa for the present-day Earth that are associated with the broad, warm structures (i.e., superplumes) in the deep mantle, consistent with previous proposals of dynamical support for the Pacific and African superswells. Our models reveal that Pangea assembly and breakup, by affecting subduction and mantle upwelling processes, have significant effects on continental vertical motions. Our models predict that the Slave craton in North America subsides before Pangea assembly at 330. Ma but uplifts significantly from 330. Ma to 240. Ma in response to pre-Pangea subduction and post-assembly mantle warming. The Kaapvaal craton of Africa is predicted to undergo uplift from ~180. Ma to 90. Ma after Pangea breakup, but its dynamic topography remains stable for the last 90. Ma. The predicted histories of elevation change for the Slave and Kaapvaal cratons compare well with the burial-unroofing histories inferred from thermochronology studies, thus supporting our dynamic models including the development of the African superplume mantle structure. The vertical motion histories for other cratons can provide further tests of and constraints on our mantle dynamic models.